The anomalous thundery month of June 1925 in SW Iberia: description and synoptic analysis - Acero, Francisco Javier; Antón, Manuel; Aparicio, Alejandro Jesús Pérez; Bravo-Paredes, Nieves; Carrasco, Víctor Manuel Sánchez; Gallego, María Cruz; García, José Agustín; Núñez, Marcelino; Tovar, Irene; Vaquero-Martínez, Javier; Vaquero, José Manuel (Copernicus Publications, 2023)
In a routine search for meteorological events with a great impact on society in the Extremadura region (SW interior of Iberia) using newspapers, the month of June 1925 was detected as exceptional due to the large number of electrical storms that occurred and the significant impacts that caused, with serious losses in human lives and material resources. This anomalous month was analyzed in detail from different, complementary perspectives: (i) the reconstruction of the history of the events, taking into account the most affected places and the most damaging impacts, from periodical publications (especially the “Extremadura” newspaper, which was the newspaper with the largest circulation in the region in 1925); (ii) the study of monthly meteorological variables (precipitation, temperature and cloudiness) of the longest series available in Iberia to highlight the exceptional nature of June 1925; and (iii) the analysis of the synoptic situation of the thunderstorms events using 20CR reanalysis data to understand from a synoptic point of view the exceptionality of this month, with a combination of a negative North Atlantic Oscillation (NAO) situation, high Convective Available Potential Energy (CAPE) values, and available water in the area.